2016 IEEE Haptics Symposium (HAPTICS) 2016
DOI: 10.1109/haptics.2016.7463193
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven thermal recognition of contact with people and objects

Abstract: Many tactile sensors can readily detect physical contact with an object, but tactile recognition of the type of object remains challenging. In this paper, we provide evidence that data-driven thermal tactile sensing can be used to recognize contact with people and objects in real-world settings. We created a portable handheld device with three tactile sensing modalities: a heat-transfer sensor that is actively heated, a small thermally-isolated temperature sensor, and a force sensor to detect the onset of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Prior works have used data-driven models to train robots how to classify common materials from thermal sensors [13], [18], [34], [35]. Kerr et al [18] used data-driven methods to train a robot to recognize materials using thermal information from the BioTac sensor, and found that the robot outperformed human participants.…”
Section: B Robot Thermal Perceptionmentioning
confidence: 99%
“…Prior works have used data-driven models to train robots how to classify common materials from thermal sensors [13], [18], [34], [35]. Kerr et al [18] used data-driven methods to train a robot to recognize materials using thermal information from the BioTac sensor, and found that the robot outperformed human participants.…”
Section: B Robot Thermal Perceptionmentioning
confidence: 99%
“…Despite not being as effective as the one stage ANN method presented in (Kerr et al, 2014a), this two stage approach obtained a classification rate of 83.81% for material group identification and 70.48% for individual material identification. Bhattacharjee et al (2016) continued their earlier research and presented a method for distinguishing between contact with inanimate objects and humans, using a novel portable handheld device developed by the authors consisting of three tactile sensing modalities: a force sensor to detect contact, a heat-transfer sensor that is actively heated, and a small thermally-isolated temperature sensor . Data was collected from the arms of 10 human subjects from 3 different locations on the right arm and 80 objects consisting of 8 similar objects from 10 different bathrooms (Bhattacharjee et al, 2016).…”
Section: Background and Related Researchmentioning
confidence: 95%
“…Bhattacharjee et al (2016) continued their earlier research and presented a method for distinguishing between contact with inanimate objects and humans, using a novel portable handheld device developed by the authors consisting of three tactile sensing modalities: a force sensor to detect contact, a heat-transfer sensor that is actively heated, and a small thermally-isolated temperature sensor . Data was collected from the arms of 10 human subjects from 3 different locations on the right arm and 80 objects consisting of 8 similar objects from 10 different bathrooms (Bhattacharjee et al, 2016). The effect of varying durations of contact made with the human subjects and the objects was also evaluated.…”
Section: Background and Related Researchmentioning
confidence: 95%
“…Some studies also used the BioTAC TM 's signal with machine learning such as Artificial Neural Network (ANN) [17] and Hidden Markov Models (HMMs) [18]. Rapid recognition estimation using learning technique is proposed in [19], extended it to the binary classification in real life [20], and developed the multimodal sensors [21].…”
Section: Introductionmentioning
confidence: 99%